Epidemiological survey of bovine tuberculosis and brucellosis in the northwest region of the State of Paraná, in the period from 2018 to 2021 (Research, Society and Development, 2022)
In view of the economic and public health importance, this study aimed to carry out an epidemiological survey, based on data from the Agricultural Defense Agency of the State of Paraná (ADAPAR), of confirmed cases of tuberculosis and bovine brucellosis in the northwest region of Brazil. state of Paraná, from 2018 to 2021. Through the monthly epidemiological reports made available by ADAPAR, a data survey was carried out, including the 62 municipalities belonging to the region, the results obtained were expressed from a simple analysis in tables using the Excel software, comparing the number of animals tested with the total number of positives and their respective percentages for each disease and year. Considering the total period from 2018 to 2019, 7,914 animals were tested for tuberculosis and of these 3.4% were positive, corresponding to 330 animals. By the annual assessment 2018 (3.3%), 2019 (2.8%), 2020 (8%), 2021 (3.4%). For brucellosis in the same period, a total of 14,264 animals were tested with a percentage of 2.33% of positives, corresponding to 332 cattle, being in 2018 (2.4%), 2019 (2.2%), 2020 (1.9 %), 2021 (5%). Despite the low prevalence of cases of brucellosis and bovine tuberculosis in the northwest region of the state of Paraná from 2018 to 2021, the health measures recommended by the PNCEBT and ADAPAR should continue to be prioritized so that the reduction and possible eradication of both diseases occurs in the coming years, ensuring the production of food of animal origin safely to the consumer market, as well as reducing economic losses with infected animals.